TLR3 and RIG-I gene variants: Associations with functional effects on receptor expression and responses to measles virus and vaccine in vaccinated infants - Clifford, H.; Yerkovich, S.; Khoo, S.; Zhang, Guicheng; Upham, J.; Le Souëf, P.; Richmond, P.; Hayden, C. (2012)
Measles virus causes severe morbidity and mortality, despite the availability of measles vaccines. Successful defence against viral pathogens requires early recognition of virus-specific patterns by innate receptors like Toll-like receptor (TLR)3 and the RNA helicase, retinoic acid inducible gene-I (RIG-I). Genetic differences in these receptors may influence the primary immune responses to measles and the efficacy of measles vaccine. In 1-year-old Australian infants after their first measles vaccine dose, we investigated functional effects of TLR3 and RIG-I polymorphisms on intracellular protein expression using flow cytometry, cytokine responses to receptor ligands and measles lysate, and post-vaccination measles IgG levels. We found that TLR3 Leu412Phe was significantly associated with IFN-a/ß response after stimulation with TLR3 ligand, poly(I:C) (P= 0.024). Downregulation of TLR3 protein expression in NK cells after poly(I:C) was also associated with this variant (P= 0.011). In contrast, measles-specific expression, cytokine responses and antibody responses were not associated with TLR3 polymorphisms. No associations were found with RIG-I variants. These results suggest that a TLR3 polymorphism has functional effects on receptor expression and cytokine response. However, this did not translate to an effect on specific responses to measles virus or vaccine. We found no evidence that RIG-I polymorphisms were involved in measles immune responses. © 2012.